Etika Bisnis Islam Komunitas Jawa,Tionghoa, dan Arab di Kota Pekalongan - Ayesha Nur Salma (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2019)
This research aims to study: 1) the analysis on the service of traders of Javanese, Chinese and Arabic community in Pekalongan City in the perspective of Islamic Business Ethics; 2) the analysis of the implementation of trade values among the traders of Javanese, Chinese, and Arabic in Pekalongan City in adapting and building the relation; and 3) the analysis about the trade relation among community of Javanese, Chinese and Arab in Pekalongan CityThe result of the research showed that first, from the service indicators, the one able to make the customers satisfied was found in the traders from Chinese ethnicity This then showed that though the Chinese ethnicity was not Moslem, in the implementation of the trade, it was not far from the Islamic teaching. Second, the values implemented by the traders from Java, Chinese and Arab traders had a specific typicality to adapt and build the relation with their customers in which the Arabic ethnicity was more dominant than Chinese and Javanese traders in all indicators. It also could facilitate the traders to adapt with the customers and build a good relation with their customers by providing the qualified commercial goods and not selling the goods below the market price as it can reduce the market price. This also could emerge a bad relation among traders either with the same or different ethnicity, not doing the stockpiling, not doing fraud in weighing and fair in determining price. Third, in social relation practice among the traders of Javanese, Chinese and Arab in Pekalongan City, there was a base of altogether interest in terms of trading. Of those three ethnicities, it could create a normal relation in daily life – not emerging any differences